Su Baltasar Gracián e il suo Oracolo manuale - Benedetti, Amedeo (Rivista di studi politici internazionali, 2022)
The paper focuses on the Oráculo Manual y Arte de Prudencia by Baltasar Gracián. We propose a pragmatic approach to Gracián’s famous book, by highlighting a few passages and comparing them with analogous statements of other great personalities, like Ignatius of Loyola and Niccolò Machiavelli. Our focus is on the aspects of Gracián’s work that are still valid today. Among these we mention the decisive role of prudence, as well as the importance in self-promotion of knowledge, of perfectionism, and of psychological observation.